(untitled) - Boyce, William E. (New York, 1986)
The environment in which instructors teach, and students learn differential equations has changed enormously in the past few years and continues to evolve at a rapid pace. Computing equipment of some kind, whether a graphing calculator, a notebook computer, or a desktop workstation is available to most students. The seventh edition of this classic text reflects this changing environment, while at the same time, it maintains its great strengths - a contemporary approach, flexible chapter construction, clear exposition, and outstanding problems. In addition many new problems have been added and a reorganisation of the material makes the concepts even clearer and more comprehensible.
Keywords: Differential equations,Boundary value problems,Phương trình vi phân,Giá trị biên